Strengthening regional collaboration: visit of Assoc. Prof. Dr. Andi Hermansyah and students from Universitas Airlangga - Abd Wahab, Mohd Shahezwan (Faculty of Pharmacy, 2025)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), through the Elderly Medication and Safety Research Interest Group, was honoured to host Assoc. Prof. Dr. Andi Hermansyah, together with Mr. Khaliq Maryono (Magister Student) and Mr. Fidi Setyawan (Doctoral Student) from the Faculty of Pharmacy, Universitas Airlangga (UNAIR), Indonesia, on 3 and 4 September 2025. The two-day visit strengthened academic and research partnerships between UiTM and UNAIR through scholarly exchange, collaborative planning, and community outreach.